Treatment volume definition for irradiation of primary lymphoma of the orbit: Utility of multimodality imaging - Selcuk Demira; Ferrat Dincoglan; Omer Sager; Murat Beyzadeoglu (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Objective: Irradiation may be utilized for management of orbital lymphomas with successful treatment results. However, adverse radiation effects may be considered as a concern particularly in the setting of higher delivered doses despite the excellent rates of tumor control in majority of irradiated patients. Multimodality imaging may serve as a contemporary approach for precise target definition in management of orbital lymphomas. Within this context, we assessed multimodality imaging based treatment volume definition for irradiation of primary lymphoma of the orbit in this original article. Materials and methods: Treatment volume definition by multimodality imaging with incorporation of MRI or by computed tomography (CT)-simulation images only was evaluated with comparative analysis in a series of patients receiving irradiation for orbital lymphoma. Results: Available treatment planning systems at our tertiary referral institution were used for precise radiation treatment planning. Prioritization was given for encompassing of the target volumes with optimal sparing of critical structures in radiation treatment planning. Synergy (Elekta, UK) LINAC was used in RT delivery. Treatment volume determination by CT-only imaging and by CT-MR fusion based imaging was assessed with comparative analysis. As a result, ground truth target volume was found to be identical with treatment volume definition with CT-MR fusion based imaging.  Conclusion: Accurate and precise target and treatment volume determination comprises an indispensable aspect of successful orbital lymphoma irradiation. Within this context, incorporation of MRI in target and treatment volume definition process may be strongly considered for improving the optimization of target and treatment volume determination for optimal irradiation. Clearly future studies are required to shed light on this issue.